Community-based seasonal movement grazing maintains lower greenhouse gas emission intensity on Qinghai-Tibet Plateau of China - Minghao Zhuang; Gongbuzeren; Gongbuzeren; Wenjun Li (Land Use Policy, 2019)
Global livestock husbandry provides ecosystem goods and services but also emits 7.1 Gt CO2-eq. of greenhouse gases (GHGs) per year. To lower GHG emissions intensity, appropriate production management systems should be identified. Since the 1980s, grassland livestock husbandry in China has transformed gradually from pastoralism into individual household management under the Grassland Household Contract System Policy. However, little is known about how this transition influences GHG emissions. We selected two case study sites representing two different forms of rangeland management systems in Ruoergai county of the Qinghai-Tibet Plateau, viz. 1) household-based all year continuous grazing under the individual use of rangeland with fences demarcating boundaries; 2) community-based seasonal grazing under the common use of the whole rangeland. The objective was to examine the differences in greenhouse gas emission intensity between the two systems using life cycle assessment (LCA). The results showed that the transition from community-based seasonal grazing into household-based continuous grazing increased the GHG emissions intensity from -0.62 kgCO2-eq/kg meat to 10.51 kgCO2-eq/kg meat. The increase was primarily attributed to changes in soil carbon storage. Findings suggest that to minimize GHG emissions and environmental degradation, community-based seasonal grazing in the pastoral area of Qinghai-Tibet Plateau should be maintained. Enhancing soil carbon sequestration by adopting appropriate practices would further reduce the GHG emissions intensity arising from the livestock system.